Guanti come dispositivi medici o come DPI: normativa vigente e corretto impiego in ambito sanitario / Gloves as medical devices or individual protection devices: current regulations and correct use in hospital environments - Feltrin, G.; Maggio, G. (La Medicina del Lavoro, 2008)
L’ambito ospedaliero a differenza d’altri ambiti occupazionali vede la presenza di un diverso soggetto costituito dall’utente. Gli operatori sanitari nella loro attività devono pertanto adoperare quelle protezioni necessarie a tutelare i pazienti ma anche se stessi. Nel caso della protezione della cute delle mani l’operatore deve saper comprendere quando utilizzare un dispositivo medicale e quando un dispositivo di protezione individuale. L’azienda ospedaliera “Ospedale civile di Vimercate” ha redatto un protocollo operativo per la fornitura e l’uso corretto delle diverse tipologie di guanti fornendo informazioni agli addetti circa le direttive europee, il marchio, le norme tecniche di riferimento, i materiali ed i livelli prestazionali di protezione. Gloves as medical devices or individual protection devices: current regulations and correct use in hospital environments Background: Hospital work consists of the care and assistance of patients, who therefore constitute another group of individuals besides the workers, which is a completely different situation compared to other workplaces in manufacturing industries. Objectives: Health professionals must know how to use the right devices to protect both the patients and themselves. In the case of protection of the hands, health professionals must also know when to use gloves as “individual protection gloves” and when to use gloves as “medical devices”, and comply with both Italian and European Community regulations. Methods and results: The Hospital of Vimercate (Milan) has drawn up technical procedures regarding the various types of gloves used in hospitals, which provide health care workers with accurate information on regulations and protocols, prevention guidelines, safety management recommendations, purchasing specifications, quality controls, correct uses of gloves and devices.